Effects of electrical stimulation‐induced resistance exercise training on white and brown adipose tissues and plasma meteorin‐like concentration in rats - Yuhei Amano; Yudai Nonaka; Reo Takeda; Yutaka Kano; Daisuke Hoshino (Physiological Reports, 2020)
Abstract Chronic endurance exercise training induces morphological and metabolic alterations including mitochondrial biogenesis in white adipose tissue (WAT) and brown adipose tissue (BAT) in rodents. A myokine called meteorin‐like (Metrnl) is associated with morphological and metabolic adaptation and increased in blood after acute resistance exercise. However, the effects of chronic resistance exercise training (RT), which aims to increase muscle mass and strength, on WAT and BAT are unclear. Therefore, we aimed to clarify the effects of RT on morphological and metabolic parameters in WAT and BAT and on plasma Metrnl concentrations. We applied electrical stimulation to both legs of rats as RT three times a week for 4 weeks. RT reduced adipocyte size in subcutaneous WAT but induced no changes in mitochondrial and thermogenesis proteins. In BAT, peroxisome proliferator‐activated receptor gamma coactivator‐1 alpha (PGC‐1α) protein levels and mitochondrial content markers were significantly higher in the RT group compared with the control group. A significant positive correlation was found between the expression of PGC‐1α in BAT and plasma Metrnl concentrations. These results suggest that plasma Metrnl is associated with PGC‐1α and mitochondrial biogenesis in BAT. This study describes a potential role of RT in preventing metabolic diseases via altering WAT and BAT and increasing plasma Mertnl concentrations.